A comparison of the habitual landing strategies from differing drop heights of Parkour practitioners (traceurs) and recreationally trained individuals - Standing, R. J.; Maulder, P. S. (Journal of Sports Science & Medicine, 2015)
Parkour is an activity that encompasses methods of jumping, climbing and vaulting. With landing being a pertinent part of this practise, Parkour participants (traceurs) have devised their own habitual landing strategies, which are suggested to be a safer and more effective style of landing. The purpose of this study was to compare the habitual landing strategies of traceurs and recreationally trained individuals from differing drop heights. Comparisons between landing sound and mechanical parameters were also assessed to gauge the level of landing safety. Ten recreationally trained participants and ten traceurs performed three landings from 25% and 50% body height using their own habitual landing strategies. Results at 25% showed significantly lower maximal vertical force (39.9%, p < 0.0013, ES = -1.88), longer times to maximal vertical force (68.6%, p < 0.0015, ES = 1.72) and lower loading rates (65.1%, p < 0.0002, ES = -2.22) in the traceur group. Maximal sound was also shown to be lower (3.6%), with an effect size of -0.63, however this was not statistically significant (p < 0.1612). At 50%, traceurs exhibited significantly different values within all variables including maximal sound (8.6%, p < 0.03, ES = -1.04), maximal vertical force (49.0%, p < 0.0002, ES = -2.38), time to maximal vertical force (65.9%, p < 0.0067, ES = 1.32) and loading rates (66.3%, p < 0.0002, ES = -2.00). Foot strike analysis revealed traceurs landed using forefoot or forefoot-midfoot strategies in 93.2% of trials; whereas recreationally trained participants used these styles in only 8.3% of these landings. To conclude, the habitual landings of traceurs are more effective at lowering the kinetic landing variables associated with a higher injury risk in comparison to recreationally trained individuals. Sound as a measure of landing effectiveness and safety holds potential significance; however requires further research to confirm